Sex ratio of the green sea turtle Chelonia mydas (Testudines: Cheloniidae) hatchlings in the Guanahacabibes Peninsula, Cuba - Calderón-Peña, Randy (2020)
Introduction: Sea turtles have temperature dependent sex determination. The increase in global temperature leads to higher nest temperatures that can cause a prevalence of females, threatening the future of these species. Objective: The present work aims to evaluate the trend of incubation temperatures and the incubation period, as well as to estimate the sex ratio in nests of Chelonia mydas at Antonio and La Barca beaches, Southwestern Cuba, during the seasons from 2012 to 2018. Methods: Temperature data loggers were placed in green turtle nests with a representativeness that varied between the years analyzed. To assess the temporal variation of temperatures and incubation periods, a Kruskal-Wallis test was performed in each case. Sex ratio was estimated from its relation with temperature and incubation duration. Results: At La Barca beach, there was a 1.5 °C increase in the mean nest temperature from 2012 to 2018, although no differences were found in the period from 2015 to 2018. At Antonio beach, there is no trend since no differences were found in the mean nest temperature except for the years 2013 and 2017, which had lower temperatures than the other seasons. In both beaches mean nest temperature exceeded 30 °C in most of the years. As a result, there was a predominance of nests with incubation periods shorter than 55 days. With these values, a female hatchling production over 90 % is expected in both study sites. Conclusions: In correspondence with the registered temperature and incubation period values, most of the years reflect a hatchling production biased towards females in both beaches.